The heist [compact disc, unabridged] : a novel - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2014)
"Legendary spy and art restorer Gabriel Allon is at work in Venice repairing an altarpiece when he receives an urgent summons from the Italian police. The art dealer Julian Isherwood has stumbled upon a murder scene in Lake Como, and is being held as a suspect. To save his friend, Gabriel must perform one simple task: Find the most famous missing painting in the world. Sometimes the best way to find a stolen masterpiece is to steal another one... The dead man is a fallen spy with a secret: he has been trafficking in stolen artworks and selling them to a mysterious collector. Among those paintings is the world's most iconic missing masterpiece: Caravaggio's Nativity with St. Francis and St. Lawrence. Gabriel embarks on a daring gambit to recover the Caravaggio that will take him on an exhilarating hunt--from Marseilles and Corsica, to Paris and Geneva, and, finally, to a small private bank in Austria, where a dangerous man stands guard over the ill-gotten wealth of one of the world's most brutal dictators" --